2016
DOI: 10.1111/ijfs.13304
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of pressurised liquid extraction for antioxidative polyphenolic compound from Momordica charantia using response surface methodology

Abstract: Pressurised liquid extraction (PLE) of antioxidant compounds from bitter gourd fruits (Momordica charantia) in aqueous ethanolic solvent was investigated using response surface methodology at laboratory scale to understand key impact of extraction variables. Extraction efficiency was optimised by measuring the yield of extraction, total phenolic content (TPC), total flavonoid content (TFC), ferric reducing/ antioxidant power assay (FRAP) and radical scavenging activity (RSA). The optimal extraction conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The use of higher temperatures enhances the mass transfer and extraction solubility of several polyphenols; however, increased temperatures ( T ° ˃ 50 °C) can also degrade thermo‐labile polyphenols such as anthocyanins (Monrad et al ., ). Therefore, these disadvantages should be taken into consideration when optimising the process (Syahariza et al ., ). Additionally, using hydroethanolic mixtures, advantages of both solvents can be utilised.…”
Section: Resultsmentioning
confidence: 97%
“…The use of higher temperatures enhances the mass transfer and extraction solubility of several polyphenols; however, increased temperatures ( T ° ˃ 50 °C) can also degrade thermo‐labile polyphenols such as anthocyanins (Monrad et al ., ). Therefore, these disadvantages should be taken into consideration when optimising the process (Syahariza et al ., ). Additionally, using hydroethanolic mixtures, advantages of both solvents can be utilised.…”
Section: Resultsmentioning
confidence: 97%
“…Extraction yield was positively influenced by temperature. This behavior can be explained by (i) improvement of mass transfer from the sample to the extraction solvent, (ii) increasing of the solubility of compounds and (iii) reduction in solvent viscosity giving more penetration of the solvent in the matrix . The composition of the solvent also showed a significant effect (see Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Syahariza et al . () found an aqueous‐alcoholic solvent mixture to promote phenolic extraction, owing to higher analyte solubility from ethanol and increased desorption from water. In the present study, it was expected that DWM extraction could combine the features of both solvents, but results showed no benefit over DW at 6 and 12 h soaking times (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Rabeta & An-Nabil (2013) observed that methanol could assist the extraction yield of polyphenols by facilitating penetration into the cell structure; however, a higher TPC was not obtained in this study. Syahariza et al (2017) found an aqueousalcoholic solvent mixture to promote phenolic extraction, owing to higher analyte solubility from ethanol and increased desorption from water. In the present study, it was expected that DWM extraction could combine the features of both solvents, but results showed no benefit over DW at 6 and 12 h soaking times (Table 1).…”
Section: Total Phenolicsmentioning
confidence: 99%